Effect of zirconia content on properties of Al7050 alloy composites by stir casting method. (2021) - Vignesh, P.; Alagarsamy, S.V.; Raveendran, P.; Saravanan, H.; Karthikeyan, K.
Abstract: Aluminium based metal matrix composites (AMMCs) are most prominence materials for using various applications like aerospace, automotive and defence industries owing to their favorable properties. The aim of the current research work involves Al7050 alloy matrix reinforced with varying 0, 4, 8 and 12 wt% of zirconia (ZrO2 ) content by using stir casting method. The effect of ZrO2 content on the properties such as hardness, tensile strength, elongation, impact strength and wear rate for the produced composites were examined. The microstructure of the proposed composite evident the uniform distribution of ZrO2 content into the matrix. The experimental result showed that the addition of 12 wt% ZrO2 particles in the Al7050 alloy enhanced the maximum strength and hardness properties. But, the elongation of produced composites gradually decreased with increasing the ZrO2 reinforcement particles. The scanning electron microscope (SEM) was employed to investigate the tensile fractography of Al7050-12 wt% ZrO2 composite. The minimum wear rate of 0.0034 mm 3 /m was achieved by the inclusion of 12 wt% ZrO2 content.